2011
DOI: 10.3390/ijms12042408
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Deficiencies and Phospholipid Metabolism

Abstract: Phospholipids are important components of the cell membranes of all living species. They contribute to the physicochemical properties of the membrane and thus influence the conformation and function of membrane-bound proteins, such as receptors, ion channels, and transporters and also influence cell function by serving as precursors for prostaglandins and other signaling molecules and modulating gene expression through the transcription activation. The components of the diet are determinant for cell functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 144 publications
1
28
0
3
Order By: Relevance
“…Magnesium is intimately involved in nucleic acid metabolism; it plays key roles in the second messenger systems that mediate hormonal effects on cells, and is a major controller of cellular ion channels, governing the flow of sodium, potassium and calcium in and out of cells [15]. It is also involved in plasma membrane phospholipid metabolism [16][17][18][19]. The altered concentration of phospholipids as a result of magnesium deficiency further affects the conformation and function of membrane-bound proteins, such as ion channels, ion pumps and receptors [16], resulting in a change in Ca 2+ influx, Ca 2+ efflux, and Ca 2+ release from intracellular stores.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Magnesium is intimately involved in nucleic acid metabolism; it plays key roles in the second messenger systems that mediate hormonal effects on cells, and is a major controller of cellular ion channels, governing the flow of sodium, potassium and calcium in and out of cells [15]. It is also involved in plasma membrane phospholipid metabolism [16][17][18][19]. The altered concentration of phospholipids as a result of magnesium deficiency further affects the conformation and function of membrane-bound proteins, such as ion channels, ion pumps and receptors [16], resulting in a change in Ca 2+ influx, Ca 2+ efflux, and Ca 2+ release from intracellular stores.…”
mentioning
confidence: 99%
“…It is also involved in plasma membrane phospholipid metabolism [16][17][18][19]. The altered concentration of phospholipids as a result of magnesium deficiency further affects the conformation and function of membrane-bound proteins, such as ion channels, ion pumps and receptors [16], resulting in a change in Ca 2+ influx, Ca 2+ efflux, and Ca 2+ release from intracellular stores.…”
mentioning
confidence: 99%
“…Conversely, as mentioned previously, the pentose phosphate pathway seemed to be activated in the RES lambs (e.g., upregulation of PRPS2), thus producing NADPH to be used in the biosynthetic pathways prevalent in the growing lambs (Wood, 1985). Together with the increased expression of genes related to nucleotides (e.g., XDH, LOC101109035, NT5E, AK7, LOC101106419, CMAS, and PRPS2), components of the cell membranes such as glycerophospholipids (e.g., PEMT; Gimenez et al, 2011), nucleoporins involved in RNA transport (e.g., NUP210, NUP62, and NDC1), ribosome biogenesis (e.g., POP7 LOC101102787, LOC101104725, and RPL22L1), and the production of vitamins and cofactors (e.g., TKFC, PNPO, NNT, BTD, SPR, LOC101103439, LOC101104703, DHRS3, LOC101119050, and BCO1), these modifications seem to be indicative of an attempt of the growing organism for maintaining natural physiological functions for growth, such as cell proliferation, differentiation, and gene expression under feed restriction conditions. Keogh et al (2016) demonstrated an increment of the expression of genes related to ribosomal functions (RPL22, RPL23, RPL26, RP6S, or POP1) that might point towards enhanced protein biosynthesis in restricted-fed animals.…”
Section: Carbohydrate Metabolic Pathwaysmentioning
confidence: 99%
“…В связи с активным преобразованием в настоящее время структуры популяций следует упомянуть о таком состоянии, как акклиматизационные микроэлементо-зы [7], и о широком распространении дефицита разно-образных микро-и макроэлементов у жителей в раз-личных странах мира [9,10]. Было установлено, что для детей со сниженным уровнем здоровья характерен выраженный дисбаланс по микро-и макроэлементам (недостаток эссенциальных (Ca, Fe, Mg и особенно Zn) и избыток токсичных) [11].…”
Section: экологическая генетика человекаunclassified